COURT COSTS AS AN INTERDISCIPLINARY INSTITUTION OF LAW: THE EXPERIENCE OF LEGISLATION AND LEGAL DOCTRINE (World Bulletin of Management and Law, 2025)
This article analyzes the legal foundations and practical significance of the institution of court costs in the economic procedural law of Uzbekistan. Court costs play an important role in ensuring a fair trial and are financed from the state budget and the costs of the participants. The concept, composition and mechanisms for reimbursement of court costs in economic courts, as well as their legal and economic essence, are considered. This article contains scientific conclusions and recommendations on the formation and development of the institution of court costs, ways to increase the efficiency of the judicial system
Keywords: State budget; economic court; court costs